Der Einfluss der Produktart und des Weiterempfehlungskanals auf den Erfolg von Weiterempfehlungen bei Versicherungen - Musiol, Andreas; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2019)
For many insurance providers referral programs are a promising customer acquisition tool. Previous research work has been widely studied successful referrals, thereby neglecting unsuccessful referrals. In an empirical study, we examine potential drivers of successful referral likelihood. In particular, we analyze the impact of tie strength (weak ties vs. strong ties) and referral channels (personal vs. written) on the likelihood of successful referrals, and the moderating role of product type (life insurance vs. non-life insurance). Based on customer data from an insurance provider, we show that the likelihood of successful referrals substantially depends on strong social ties (i.e., both the referring and the referred person are living in the same household). Further, a positive interaction effect between tie strength and product type reveals that successful referral likelihood is not merely a result of tie strength: Strong-tie (weak-tie) referrals yield higher (lower) successful referral likelihood for life insurances as compared to non-life insurances. Finally, we show that successful referral likelihood also depends on the choice of the referral channel. Referrals that are mentioned across verbal (written) referral channels yield higher (lower) successful referral likelihood for life insurances as compared to non-life insurances.
CRIS-Team Scopus Importer:2019-07-09